Misja Kościoła — niezwykła zwykłość nauczania papieża Franciszka - Gardocki, Dariusz (Poznańskie Studia Teologiczne, 2020)
With Pope Francis a new chapter has begun in the history of the Church. This newness refers to the new internal situation of the Church, new “signs of time”, and new challenges which the Church has to face. Through the symbolic gestures of his pastoral practice and the directions indicated in his homilies and encyclical letters Francis responds to these challenges in the spirit of the Gospel. His whole pontificate is characterized by the profound desire to impart the newness and fresh- ness of the Gospel as well as what constitutes the core of its teaching. In this endeavor of returning to the sources, he sees the possibility of renewal of the Church. This entails a discernment of what constitutes the center and core of the Christian proclamation versus what is secondary, as well as how Jesus’ teaching has been distorted and deformed over the centuries. Francis speaks about the necessity of the apostolic and pastoral conversion of the Church. The Church has to undertake the “option for mission” and “apostolic dynamism”. She must go to the peripheries. In his teaching Pope Francis imparts the traditional doctrine of the Church. But he does it in a new way, using new language, new gestures and a new way of life. Like his predecessors, he wants to serve the faith. He does not wish to change what constitutes the core of the Christian faith. But he wants the Church to grow in the understanding of the Gospel as well as in the discernment of the ways of the Spirit. Therefore, he emphasizes the constant need for the attitude of discernment. This is what he has learned above all from Ignatian spirituality and his pastoral experience: “the discernment of the spirits”.